Protective Effect of Urtica dioica Seeds’ Extract in Experimental Chronic Aflatoxicosis in Broiler Chickens - Ayna, Erhan; Huyut, Zübeyir; Keleş, Omer Faruk; Yener , Zabit; Bal, Ramazan (International Journal of Poultry Science, 2021)
Background and Objective: Aflatoxins can lead to Aflatoxicosis in animals and humans. The aim of this study was to investigate hepatoprotective and antioxidant effect of Urtica dioica seeds’ extract (UDSE) on chronic aflatoxicosis in broiler chickens, which were evaluated by histopathologically liver degeneration and activities/levels of the oxidative stress and antioxidant parameters. Materials and Methods: Thirty-two broiler chickens were randomly divided into four experimental groups: control group served as a negative control and were fed with a normal diet; AFB1 group received aflatoxin B1 (AFB1) (1 mg kg–1 diet) for 42 days; UDSE group received UDSE (30 mL kg–1 diet) for 42 days and AFB1+UDSE group received AFB1 (1 mg kg–1 diet) as well as UDS extract (30 mL kg–1 diet) for 42 days. Results: In the AFB1 group, activities of SOD, GSH-Px and CAT and the levels of TAS and BcL-2 in liver and serum were significantly lower than that of the control group (p<0.001), TOS and Caspase-3 levels were also significantly high (p<0.001). Whereas, in the AFB1+UDSE group, the activity of GSH-Px in liver and serum and the activities of SOD and CAT and the level of TAS in serum were significantly higher than those in AFB1 group (p<0.001). In the AFB1+UDSE group, the levels of TOS and Caspase-3 were significantly lower (p<0.001) and the level of BcL-2 were higher in both liver and serum compared to those of the AFB1 group (p<0.001). Histopathologically, diffuse hydropic degenerations, periportal fibrosis and activation of perisinusoidal myofibroblastic (Ito) cells were observed in the AFB1 group. These morphological changes were reduced significantly in the AFB1+UDSE group. Conclusion: The UDSE has a protective effect on chronic aflatoxicosis in broiler, which appear to be attributable to its antioxidant and anti-apoptotic activity.